2004
DOI: 10.1103/physreve.70.016403
|View full text |Cite
|
Sign up to set email alerts
|

Third-harmonic generation in the skin layer of a hot dense plasma

Abstract: The third-harmonic generation of a pump wave, resulting from the electron-ion collision frequency dependence on the electric field in the skin layer of a hot dense plasma is investigated. The relation of the current third harmonic with the high-frequency field in the skin layer is established for arbitrary ratios of the electron-ion collision frequency to the field frequency. For arbitrary ratios of these two frequencies, the field structure inside the skin layer is determined, and the field of the wave irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…͑11͒ and ͑12͔͒ does not coincide with that of the fundamental wave, but the propagation direction is the same. Generation efficiency increases with the beam density increase and reaches the maximum at N b ϳ N. As in the theory of harmonics generation due to electron-ion collisions, [12][13][14][15] ͑2͒ and ͑3͒ reach their largest values when v E is of the order of magnitude as u. The further v E increase leads to the generation efficiency weakening as the electron effective collision frequency diminishes as ͑v E ͒ϳv E −3 .…”
Section: ͑1͒mentioning
confidence: 91%
“…͑11͒ and ͑12͔͒ does not coincide with that of the fundamental wave, but the propagation direction is the same. Generation efficiency increases with the beam density increase and reaches the maximum at N b ϳ N. As in the theory of harmonics generation due to electron-ion collisions, [12][13][14][15] ͑2͒ and ͑3͒ reach their largest values when v E is of the order of magnitude as u. The further v E increase leads to the generation efficiency weakening as the electron effective collision frequency diminishes as ͑v E ͒ϳv E −3 .…”
Section: ͑1͒mentioning
confidence: 91%
“…[1][2][3][4][5][6][7] It is observed that harmonic yield is significantly enhanced in the presence of surface roughness or nanostructures. [8][9][10][11][12][13][14] This enhancement is attributed to laser mode conversion into surface plasma wave (SPW), an electromagnetic mode, propagating close to metaldielectric interface with sharp decay of amplitude in both mediums away from the interface.…”
Section: Introductionmentioning
confidence: 94%
“…For example, the highly non-linear nature of the interaction of laser pulses with gases and plasmas implies that harmonic light should be a significant feature of such interactions. [7][8][9] Several mechanisms can generate laserharmonics in plasmas such as density-gradients in plasma or by applying external magnetic fields. In the harmonic generation process, two photons of energy hx 1 and momentum hk 1 combine to produce a photon of higher harmonic radiation with energy hx 2 and momentum hk 2 , where ðx 1 ;k 1 Þ are the frequency and wave vector of the fundamental wave and ðx 2 ;k 2 Þare the frequency and the wave vector of the secondharmonic wave, which satisfy the linear dispersion relation for electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%